Expenses Claim System (ECS) / Lim Foung Wan - Lim, Foung Wan (2003)
Expenses Claim System (ECS) is basically a system, which makes the process of claiming faster and easier for the staff of the Faculty of Computer Science and Information Technology (FSKTM). ECS is intended to provide a computer-based system for claiming process. Besides that, ECS provides a user friendly application. Users are able to access to ECS at anytime of the day. ECS consists of two modules. First, which is the user module, provides the facility of accessing to the claiming form, viewing claim rates of claiming by the University and changing the password. The second module is the approver module. This module provides the facility of viewing claim rates, approving or rejecting the claim application and changing the password. The system is expected to save time as the details of the staff is automated and this prevents the user from referring to documentation to complete the expenses claim form. The information of the staff is secured as the data and information are kept in a database that is effective and efficient. ECS is to be developed using Active Server Pages (ASP) and Microsoft SQL Server 2000. Active Server Pages is used to create user friendly interface while Microsoft SQL Server 2000 is for storing information in database. Both works well when integrated.